1998
DOI: 10.1007/bf02386669
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and utilization of potassium nickel hexacyanoferrate for the separation of cesium and cobalt from contaminated waste water

Abstract: A method for the preparation of potassium nickel hexacyanoferrate complex K2NiFe(CN)6.3H20 (KNiFC) with acceptable properties was developed. The complex was characterized by its solubility in different nitric acid media, thermal stability, IR spectrometry, X-ray diffraction, and scanning electron microscopy. Utilization of the prepared potassium nickel hexacyanoferrate as ion exchanger for the removal of cesium and cobalt from radiocontaminants on laboratory scale using fixed bed technique was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Various methods can be used for synthesis of ferrocyanides: precipitation of sediments with further granulation by freezing or drying [1,2], precipitation of ferrocyanides onto surfaces of inert supports (glass, silica gel, alumogel, cellulose, polyethylene terephthalate, polypropylene membranes) [3,4], modification of sorption active supports (ion exchange resins, aluminosilicates, hydrated oxides) by ferrocyanides [5][6][7][8][9], synthesis of composition sorbents including ferrocyanides of transition metals and silica gel [10,11], sol-gel method [12]. The detail review of methods of synthesis of sorbents (including ferrocyanides) can be found in the work [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods can be used for synthesis of ferrocyanides: precipitation of sediments with further granulation by freezing or drying [1,2], precipitation of ferrocyanides onto surfaces of inert supports (glass, silica gel, alumogel, cellulose, polyethylene terephthalate, polypropylene membranes) [3,4], modification of sorption active supports (ion exchange resins, aluminosilicates, hydrated oxides) by ferrocyanides [5][6][7][8][9], synthesis of composition sorbents including ferrocyanides of transition metals and silica gel [10,11], sol-gel method [12]. The detail review of methods of synthesis of sorbents (including ferrocyanides) can be found in the work [13].…”
Section: Introductionmentioning
confidence: 99%
“…Common description of the following main sorption processes possible for ferrocyanides can be found in [23]: ion exchange (equivalent exchange of ions), molecular adsorption (uptaking of equivalent quantities of anions and cations of salts by a sorbent), electron exchange (uptaking or escape of ions by a sorbent connected with reduction or oxidation of ions entering into the composition of sorbent's matrix), heterogenous ion-exchange reaction (equivalent exchange of ions, formation and development of a new phase, coexistence of two phases during the reaction; such processes are usually irreversible, degree of transformation strongly depends on temperature, sorption isotherms have the peculiar appearance). In the work [2] the influence of temperature on sorption of caesium is described and supposition about the presence of irreversible heterogenous ion-exchange reaction on ferrocyanides is made.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on the stability of the complexes used indicated that KCFC is more stable in alkaline media, while AMP is stable in acidic media;12 hence, the choice of conditions for the present study.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates stronger cesium immobilization in the KCFC complex than in the AMP complex in the leachants used. From a previous study on the reaction of Cs ions with potassium nickel hexacyanoferrate,12 denoted by KNiFC (an analog of KCFC complex), it was found that formation of the resultant compound was accompanied by structural changes. Those changes were associated with a decrease in cesium recovery from the loaded complex.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of sorption of alkali metal and ammonium ions onto normal cobalt(II) ferrocyanide proved inadequacy of the diffusion mechanism of the sorption [2]; also, Dubrovin et al [3] found that the sorption occurred by the mechanism of a heterogeneous ion-exchange reaction. Ismail et al [4] also assumed the occurrence of irreversible heterogeneous ion-exchange reaction in sorption of cesium and cobalt onto nickel potassium hexacyanoferrate [4]. The prevalent mechanism of cesium sorption onto tin ferrocyanide is molecular sorption [5] accompanied by interaction of cations and anions not only with the sorbent surface, but also with each other.…”
mentioning
confidence: 99%